Entomopathogenic fungi biomass production and extracellular biosynthesis of silver nanoparticles for bioinsecticide action - Santos, Tárcio S. (2021)
Entomopathogenic fungi are microbial agents of insect control in nature. They have been used as biologic strategies to manage insect invasion; however, the challenge is to maintain their shelf life and viability when exposed to high temperatures, ultraviolet radiation, and humidity. Synthesized silver nanoparticles (AgNPs) from fungal extracellular enzymes are an alternative using these microorganisms to obtain nanoparticles with insecticidal action. The present study evaluates the biomass production and the potential to synthesize silver nanoparticles using entomopathogenic fungi isolates. Sixteen isolates of entomopathogenic fungi were used in this study. The fungi pathogenicity and virulence were evaluated using the insect model Tenebrio molitor, at a concentration of 5 × 106 conidia/mL. The fungal biomass was produced in a liquid medium, dried, and weighed. The synthesis of silver nanoparticles was performed with aqueous extracts of the entomopathogenic fungi and silver nitrate solution (1 mM), following characterization by a UV/vis spectrophotometer, mean size, and polydispersity index. The results showed a significant variation in pathogenicity, virulence, and biomass production among the evaluated fungi isolates; however, only one of the isolates did not have the potential to synthesize silver nanoparticles. Pearsons correlation showed significant correlation values only between virulence × biosynthesis potential and biomass production × biosynthesis potential, both with negative values, indicating an inverse correlation. Thus, AgNPs with entomopathogenic fungus extract can produce an innovative bioinsecticide product using a green production process.